2019
DOI: 10.5812/pedinfect.83565
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B s-Antigen Seroconversion Rate After Primary Immunization Series with Newly Introduced Pentavalent Vaccine: A Report of Regional Study in Alborz Province, Iran, 2016

Abstract: Background: Since November 2014, pentavalent vaccine is available in Iran. This vaccine should be injected into all Iranian children at two, four, and six months after birth. Objectives: There is little information on the immunogenicity of this vaccine against hepatitis B (HB) in Iranian children; therefore, the current study aimed at investigating the vaccine efficacy six months after administration of the last dose. Methods: A total of 400 blood samples were collected from one-year-old children referred to K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This result is also supported by several other studies. Arjmand et al [ 19 ] reported that administration of three doses of hepatitis B vaccine in a pentavalent vaccine resulted in protection against 98.3% (393 children) of the total subjects (400 children). Vaccine administration routes could also affect immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…This result is also supported by several other studies. Arjmand et al [ 19 ] reported that administration of three doses of hepatitis B vaccine in a pentavalent vaccine resulted in protection against 98.3% (393 children) of the total subjects (400 children). Vaccine administration routes could also affect immunogenicity.…”
Section: Discussionmentioning
confidence: 99%